Host-pathogen interaction in arthropod vectors: Lessons from viral infections - Perveen, Nighat; Muhammad, Khalid; Muzaffar, Sabir Bin; Zaheer, Tean; Munawar, Nayla; Gajic, Bojan; Sparagano, Olivier Andre; Kishore, Uday; Willingham, Arve Lee (Frontiers in Immunology, 2023)
Haematophagous arthropods can harbor various pathogens including viruses, bacteria, protozoa, and nematodes. Insects possess innate immune system comprising both cellular and humoral components to fight against various infections. Haemocytes, the cellular components of haemolymph, are central to the insect immune system as their primary functions include phagocytosis, encapsulation, coagulation, detoxification, and storage and distribution of nutritive materials. Plasmatocytes and granulocytes are also involved in cellular defense responses. Blood feeding arthropods, such as mosquitoes and ticks, can harbour a variety of viral pathogens that can cause infectious diseases in both human and animal hosts. Therefore, arthropod vectors are important constituents of the ecosystem and it is imperative to study the virus-vector-host relationships. Regardless of the complex immune response of these arthropod vectors, the viruses usually manage to survive and are transmitted to the eventual host. A multidisciplinary approach utilizing novel and strategic interventions is required for the control of ectoparasite infestations and blocking vector-borne transmission of viral pathogens to humans and animals. In this review, we briefly discuss the arthropod immune response to viral infections with primary focus on the innate immune responses of ticks and mosquitoes. We aim to summarize critically these vector immune systems and their infection transmission strategies to mammalian hosts to foster debate that could help in developing new therapeutic strategies to protect human and animal hosts against arthropod-borne viral infections.